Intelligent Routing Technology for Multi-terminal Access in Integrated Network - XU Yi-ming, MA Li, FU Ying-xun, LI Yang, MA Dong-chao (Jisuanji kexue, 2022)
Aiming at the problem of network load balancing caused by the drastic fluctuation of network traffic caused by the access of a large number of terminal devices in the integrated heterogeneous network,an intelligent routing algorithm TDANRA based on reinforcement learning is proposed.Fine-grained and high-precision network traffic status parameters are obtained by software-defined network technology,TDANRA algorithm automatically generates real-time routing policies based on network traffic status and link bandwidth utilization threshold adjustment mechanism to guide the forwarding of network traffic,so as to solve the problem of drastic fluctuation of network traffic.Simulation results show that TDANRA algorithm can realize load ba-lancing of network traffic and reduce end-to-end transmission delay and data packet loss rate when a large number of terminal devices are connected to the network.